Psychiatrization in mental health care: The emergency department - Beeker, Timo (Frontiers in Sociology, 2022)
Background In the light of high incidences of diagnosed mental disorders and the growing utilization of mental healthcare services, a progressing psychiatrization of society has been hypothesized as the underlying dynamic of these developments. Mental healthcare institutions, such as psychiatric hospitals, may play a decisive role in this. However, there is a scarcity of research into how psychiatrization emerges in hospital settings. This paper explores whether the emergency department (ED) can be considered as a site where psychiatrization happens, becomes observable, and which factors in the context of the ED may be its potential drivers. Methods Two cases as encountered in an interdisciplinary ED will be presented in the following in an anonymized way. Although the cases originate from individual consultations, they can be considered as prototypical. The cases were collected and discussed using the method of interactive interviewing. The results will be analyzed against the backdrop of current theoretic concepts of psychiatrization. Findings The ED can be seen as an important area of contact between society and psychiatry. Decisions whether to label a certain condition as a “mental disorder” and to therefore initiate psychiatric treatment, or not, can be highly difficult, especially in cases where the (health) concerns are rather moderate, and clearly associated with common life problems. Psychiatrists' decisions may be largely influenced in favor of psychiatrization by a wide array of disciplinary, institutional, interpersonal, personal, cultural, and social factors. Conclusions The ED appears to be a promising field for research into the mechanisms and motives through which psychiatrization may emerge in mental healthcare settings. Psychiatrists in the ED work within a complex sphere of top-down and bottom-up drivers of psychiatrization. Encounters in the ED can be an important step toward adequate support for many individuals, but they also risk becoming the starting point of psychiatrization by interpreting certain problems through the psychiatric gaze, which may induce diagnoses of questionable validity and treatment of little use.